Effects of surface roughness on thermo-mechanical fatigue life of a P91 power plant steel - Kyaw, Si Thu; Rouse, James Paul; Lu, J.; Sun, Wei (Elsevier, 2016)
P91 martensitic steel has now been widely used for power plant components such as steam pipe sections and headers. With the shift to renewable sources, traditional fossil power plants are increasingly expected to operate under so called “two shifting” conditions (high frequency start up/shut down cycles from a partial load condition) to match market demands. Such conditions increase the potential for large thermal stresses to be induced in thick walled components, making thermo-mechanical fatigue (TMF) and creep-fatigue interaction a life limiting concern. It is important to investigate the behaviour of P91 power plant steel under cyclic creep-fatigue interaction conditions in order to estimate the component remnant life under various possible operating strategies. Specimens used for TMF testing are commonly hollow (unlike solid specimens used in isothermal tests) to allow for higher cooling rates (with insignificant radial temperature variations) by injecting air. It is difficult to polish the internal surface to the same extent as the external surface of the specimen (with a roughness (Ra) of 0.8μm). Concerns have been expressed as to whether this type of uncontrolled surface roughness could significantly affect the fatigue life of the specimen since most fatigue cracks often initiate at the surface of the material. In this work, the roughness profile of the internal surface of the TMF sample is measured using Alicona optical profilometer. Resultant surface profiles are idealised and used to simulate distributions of stress and plastic strain under fatigue load using multi-axial visco-plasticity model. Concentration of stress and higher plastic stain accumulations are observed at the peak region of the roughness profile and crack initiations are expected to occur at those regions. Using accumulated plastic strain as a failure criterion for the fatigue, shorter fatigue lifetime is expected for specimen with rougher surface relative to the polished specimen. Optical and scanning electron microscopy (SEM) has been used to investigate the nature of the cracks initiating from the internal and external (polished) surfaces of a failed TMF test specimen.